State-specific, racial and ethnic heterogeneity in trends of firearm-related fatality rates in the USA from 2000 to 2010. Issue 8 (August 2014) - Kalesan, Bindu; Vasan, Sowmya; Mobily, Matthew E; Villarreal, Marcos D; Hlavacek, Patrick; Teperman, Sheldon; Fagan, Jeffrey A; Galea, Sandro
Abstract : Objectives: To document overall, racial, ethnic and intent-specific spatiotemporal trends of firearm-related fatality rates (FRF rates) in the USA. Design: Cross-sectional study per year from 2000 to 2010. Setting: USA. Participants: Aggregate count of all people in the USA from 2000 to 2010. Outcome measures: Data from the Web-based Injury Statistics Query and Reporting System from 2000 to 2010 was used to determine annual FRF rates per 100 000 and by states, race, ethnicity and intent. Results: The average national 11-year FRF rate was 10.21/100 000, from 3.02 in Hawaii to 18.62 in Louisiana: 60% of states had higher than national rates and 41 states showed no temporal change. The average national FRF rates among African-Americans and Caucasians were 18.51 and 9.05/100 000 and among Hispanics and non-Hispanics were 7.13 and 10.13/100 000; Hispanics had a decreasing change of −0.18, p trend<0.0001. In states with increasing trends (Florida and Massachusetts), Caucasians and non-Hispanics drove the rise; while in states with decreasing trends (California, North Carolina, Arizona, Nevada, New York, Illinois, Maryland), Hispanics and African-Americans drove the fall. The average national FRF rates due to homicides (4.1/100 000) and suicides (5.8/100 000) remained constant, but varied between states. Conclusions: Endemic national FRF rates mask a wide variation in time trends between states. FRF rates were twice as high in African-Americans than Caucasians but decreased among Hispanics. Efforts to identify state-specific best practices can contribute to changes in national FRF rates that remain high.